Proposed Decision to Modify the New Arrangements to Borrow. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This paper examines cross-country perspectives on economies with large banking systems relative to GDP. As such economies tend to have domestic institutions with major foreign currency cross-border activities, strong links are generated between the health of the financial system and sovereign sustainability. These links are of central interest to the paper. It does not cover off-shore centers as their international links tend to be relatively unrelated to domestic activities. To make the analysis more concrete, the experience of five economies-Hong Kong SAR, Iceland, Ireland, Singapore, and Switzerland-are featured (plus a Box on the Benelux region). These economies had large and relatively diversified international banking sectors compared to their fiscal capacity before the global financial crisis of 2007-09, and divergent experiences over the crisis. The paper analyzes the reasons for these outcomes. (A range of private and public sector individuals were interviewed during missions to Belgium, Hong Kong SAR, Ireland, Singapore, Switzerland, and the United Kingdom.).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet